Use and limitations of noninvasive and invasive methods for studying pulmonary function. (2019) - Castro, Juciane Maria de Andrade; Russo, Momtchilo
Abstract : This mini-review aims to critically discuss the advantages and disadvantages of invasive versus noninvasive methods used to access pulmonary function especially in mice models of lung diseases. We briefly discussed the differences between both methods in handling expertise, number of mice required, length of time to determine lung function and anesthetic and/or use of muscle relaxant. Since noninvasive method received more criticisms than invasive method, we discussed critically the seminal studies that lend support to the disapproval of that method as measure of lung function. We show that the criticisms to the use of noninvasive method are biased or exaggerated and in general not hampered by experimental data obtained in several studies. Accordingly, in many studies the invasive method confirmed the results obtained with noninvasive method indicating that at practical level both methods were more coincident than discordant. Since both methods for measuring lung function have limitations and merits, we suggest that depending on focus of the study one method could be more adequate than the other. In studies where lung mechanical function is the main focus, the invasive method might be required. However, when determination of lung function is just one parameter among several others that characterizes lung disease, the noninvasive method might fit better since it allows performing longitudinal determinations of lung function followed by other lung pathologic parameters using smaller numbers of animals. Finally, in some studies the noninvasive method could be used to screen different experimental protocols and then the invasive method applied to confirm the positive results.